REFLECTIONS ON THE BIRTHPLACE OF AMIR TEMUR - Ko‘paysinova Nargiza Karimovna (Web of Journals Publishing, 2025)
Amir Temur, one of the most famous military leaders in the world, fully demonstrated his extraordinary military leadership skills granted by God, becoming an unparalleled great army commander, a statesman, and a patron of science and culture – recognized as the founder of the Second Renaissance. During his time, he successfully defeated all his rivals and became the ruler of Movarounnahr. He is remembered in history as the founder of the empire known as the Timurids dynasty. His vast empire stretched from India and China to the Black Sea, covering regions from the Aral Sea to the Persian Gulf, including parts of Small Asia, Syria, Egypt, the lower the Volga, the Don, the area around Lake Balkhash, the Elsuvi River, and Northern India, establishing a great state.
Keywords: Renaissance, empire, manuscript, historian, place of birth,, author, court, dynasty, village army, independence.